The Phenomenon of Cyberbullying and Its Impact on the Formation of Civic Character in Generation Z - Ni’ma Kamalia; Hidayatul Maulidia; Muhammad Rofi Ardiansyah; Innayatul Laili (Insan Akademika Publications, 2026)
The development of digital technology has shaped the interaction patterns of Generation Z, yet it has also increased the risk of cyberbullying, which poses serious impacts on their psychological, social, and civic character development. This study aims to identify the forms of cyberbullying experienced by Generation Z, analyze its effects on emotional development, social relationships, academic performance, and examine its implications for the formation of digital citizenship character. This research employs a literature review (library research) method by examining national and international journals, institutional reports, and relevant scientific publications selected through a systematic screening process. Illustrative cases involving public figuressuch as the cyberbullying experienced by TikTok influencer Fujianti Utami are used as contextual examples without serving as the main data source. The findings show that common forms of cyberbullying include flaming, harassment, denigration, impersonation, and trickery, all of which contribute to anxiety, insecurity, lower self-esteem, social isolation, difficulty concentrating, and decreased learning motivation. Long-term impacts are also evident in the formation of civic character, including weakened empathy, reduced self-control, diminished critical thinking skills, and declining social responsibility in digital spaces. These findings affirm that cyberbullying is not merely an interpersonal issue but also a threat to the development of smart, ethical, and responsible digital citizens. This study recommends strengthening value-based digital literacy, promoting social media ethics education, and enhancing collaboration among families, schools, government, and digital platforms to create a safe and civil digital environment.